Influence of the physical state of water in the diffusion process in asphalt binders - Vasconcelos, Kamilla Lima; Bhasin, Amit; Little, Dallas N.; Glover, Charles (Transportes, 2012)
Moisture damage in asphalt mixtures is a complex phenomenon that involves mechanical, chemical, physical and thermodynamic processes. This damage contributes significantly to the premature deterioration of asphalt pavements, which leads to extra cost in highway maintenance and vehicle operations. One key mechanism of how moisture reaches the asphalt-aggregate interface is by its permeation or diffusion through the asphalt binder or mastic. For the asphalt-water system studied, the Fourier Transform Infrared (FTIR) – Attenuated Total Reflectance (ATR) spectrometry was used. Water shows strong absorption in the infrared region and the FTIR-ATR technique has the ability to monitor both the kinetics of moisture ingress as well as any chemical changes occurring during the test. This paper has the literature review and some results obtained in the comparison between water diffusion in the liquid state with the moisture (or vapor) state, both at room temperature.